55th AIAA Aerospace Sciences Meeting 2017
DOI: 10.2514/6.2017-1573
|View full text |Cite
|
Sign up to set email alerts
|

MVP-Workshop Contribution: Modeling of Volvo bluff body flame experiment

Abstract: The Volvo burner features the canonical configuration of a bluff-body stabilized premixed flame. This configuration was studied experimentally under the Volvo Flygmotor AB program. Two cases are considered in this study: a non-reacting case with an inlet flow speed of 16.6 m/s and a reacting case with equilibrium ratio of 0.65 and inflow speed of 17.3 m/s. The characteristic vortex shedding in the wake behind the bluff body is present in the non-reacting case, while two oscillation modes are intermittently pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
4

Relationship

4
5

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 32 publications
2
10
0
Order By: Relevance
“…4 in Giacomazzi et al [72], Cocks et al [73], and perhaps also Baudoin et al [74]). This latter predominantly symmetric shape appears to be the physically correct one for the present boundary conditions because many of the most recent simulation studies show this shape [75][76][77][78][79]. The cause for the transition from symmetric to asymmetric flame shape seen in the present simulations may be the use of a low-Mach-number formulation instead of a fully-compressible one [77].…”
Section: Configurationsupporting
confidence: 51%
“…4 in Giacomazzi et al [72], Cocks et al [73], and perhaps also Baudoin et al [74]). This latter predominantly symmetric shape appears to be the physically correct one for the present boundary conditions because many of the most recent simulation studies show this shape [75][76][77][78][79]. The cause for the transition from symmetric to asymmetric flame shape seen in the present simulations may be the use of a low-Mach-number formulation instead of a fully-compressible one [77].…”
Section: Configurationsupporting
confidence: 51%
“…The unstructured solver, CharLES x , is employed in this study [48,49]. A finite volume approach is utilized for the discretization of the system of equations, Eq.…”
Section: Methodsmentioning
confidence: 99%
“…Theory and recent computational results have shown that for turbulent flows at low and moderate Mach numbers, an increase in polynomial order ( -refinement) is more effective in capturing turbulence characteristics, while for highly compressible turbulence regimes, ℎ-refinement becomes beneficial for representing shows and flow-discontinuities. Significant progress has been made on extending DG-methods for reacting turbulent flows [60][61][62][63]. However, in order to fully utilize the potential of these high-order variational methods for simulating turbulent flows [64][65][66][67], open research issues remain regarding the formulation of stabilization techniques, the development of combustion-physical models, and the construction of subgrid-closures that are consistent with the high-order discretization for large-eddy simulations.…”
Section: What Is the Impact Of The Numerical Discretization On Thmentioning
confidence: 99%